EVALUATION OF MANDIBULAR HARD AND SOFT TISSUES IN CLEFT PATIENTS* - Işıl ARAS; Derya BAYKAL; Merve BULUT; Servet DOĞAN (Istanbul University, 2017)
Purpose: The aim of this study was to compare the mandibular hard and soft tissue measurements of unilateral and bilateral cleft lip and palate patients with non-cleft individuals. Materials and Methods: The study sample comprised of lateral cephalograms of 45 subjects. Sample included 15 non-cleft (NC), 15 unilateral cleft lip and palate (UCLP) and 15 bilateral cleft lip and palate (BCLP) cases whose age were between 15 to 17. 1 angular 13 linear measurements were carried out using Arnett and Gunson soft tissue cephalometric analysis and 4 angular measurements were calculated with Steiner Analysis. Results: Mandibular incisor inclinations relative to the occlusal plane (Md1-Md OP) were significantly greater and mandibular incisor projections (Md1-TVL) were significantly retrusive in cleft subjects (p<0.05). Projection values pertaining to lower lip anterior (LLA-TVL), soft tissue B point (B'-TVL), and soft tissue pogonion (Pog'-TVL) were significantly deficient as well in cleft patients (p<0.05). Sagittal position of the maxilla (SNA) (p<0.001) and intermaxillary relation of the jaws (ANB) were significantly deficient in UCLP subjects (p<0.05) and BCLP individuals (p<0.01). LLA-TVL and B'-TVL correlated with SNB in cleft patients (p<0.05). Conclusion: Decreased lower lip and chin projection values suggest that mandibular region of cleft patients should be taken into account in forming the treatment plan to improve the esthetic outcome of orthodontic and plastic surgery interventions.